Nilai-Nilai Pendidikan Karakter pada Novel “Edensor” (Novel Ketiga dari Tetralogi Laskar Pelangi) Karya Andrea Hirata - Dwi Pulsha Apriliande (Estetik, 2024)
This study aims to describe the 9 pillars of character education values contained in the novel “Edensor” by Andrea Hirata. A number of steps to analyze this research are (1) reading novels, (2) trying to understand, (3) analyzing novel stories can be known, (4) making discussions, (5) drawing conclusions. The results of this study show that the 9 pillars of character education values contained in the novel “Edensor” (1) amounted to 18 citations at the elementary school, (2) amounted to 9 citations at the junior high school, (3) amounted to 15 citations at the high school, and (4) amounted to 46 citations at the college. This study concluded that after being tested by analyzing the novel “Edensor”, it is hoped that this scientific work will be able to provide accurate and relevant information about the value of character education contained in this novel.